A Comparison of Science Integration Implementation in Two State Islamic Universities in Indonesia - Sayuti, Wahdi; Rahiem, Maila D.H. (Madania: Jurnal Kajian Keislaman, 2020)
The transformation of IAIN (State Institute for Islamic Studies) into UIN (State Islamic University) cannot be isolated from discourses on identity, concepts, aspirations of the standard of Islamic education and its goal to incorporate the principle of integration of science. However, since the transformation of these institutions, the integration of science practice still appears at the normative-philosophical level and is not yet in the empirical-implementation domain. The aim of this study is, therefore, to reveal and explain the implementation of the integration of the science concept at the technical-operational level, which focuses on the curriculum design and learning process at UIN Syarif Hidayatullah Jakarta and UIN Maulana Malik Ibrahim Malang. The results of the study showed that these two universities have similarities in the concept of the integration of science and have almost the same objectives, i.e., decreasing the dichotomy of science between religious and general science. However,  UIN Maulana Malik Ibrahim Malang has a more organized and structured approach to the idea of integration, from theory and framework to the practice of curriculum design and the learning process. Perubahan status kelembagaan dari Institut Agama Islam Negeri (IAIN) menjadi Universitas Islam Negeri (UIN) tidak bisa dilepaskan dari  diskursus tentang identitas, gagasan, ekspektasi terhadap mutu lembaga pendidikan Islam dan sekaligus mengemban misi tentang pentingnya integrasi keilmuan. Namun demikian, sejak perubahan status kelembagaan ini, integrasi keilmuan yang dikembangkan di UIN ini nampaknya masih berada pada tataran normatif-filosofis dan belum menyentuh wilayah yang lebih empirik-implementatif. Oleh karenanya, penelitian ini bertujuan untuk mengungkap dan menjelaskan implementasi integrasi keilmuan ke dalam tataran yang lebih teknis operasional, yang dalam penelitian ini difokuskan pada pengembangan kurikulum dan proses pembelajaran di UIN Syarif Hidayatullah, Jakarta dan UIN Maulana Malik Ibrahim, Malang. Hasil penelitian menunjukkan bahwa secara substantif, kedua perguruan tinggi Islam memiliki kemiripan konsep integrasi keilmuan dan memiliki tujuan yang hampir sama, yakni menghilangkan dikotomi keilmuan, antara ilmu agama dan ilmu umum. Namun, jika dibandingkan antara UIN Syarif Hidayatullah Jakarta dan UIN Maulana Malik Ibrahim Malang, maka UIN Maulana Malik Ibrahim Malang dinilai lebih terencana dan sistematis dalam merumuskan konsep integrasi keilmuannya, dari mulai perumusan konsep dan paradigma sampai pada operasionalisasi penyusunan kurikulum dan proses pembelajaran.